STRATEGI PENYEDIAAN RUANG TERBUKA HIJAU PUBLIK BERDASARKAN JUMLAH PENDUDUK DI KOTA BANDAR LAMPUNG TAHUN 2021-2030 - Nikolaus Saras Kurniawan; Sandi Asmara; Adnin Musadri Asbi (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
One important element in the region is the existence of green open space, especially public green open Spaces that have ecological, cultural, economic, aesthetic, and also urban/regional. The need for public green open space as a means of recreation and community interaction is not balanced with the number of available public green open spaces that can balance the population. The public green open space affects the number of people, the more people in one city the need for green open space increases. This method of research analysis is a SWOT analysis in which in research results from the public green open space analysis, population projections, and land use & gravelly. The results are a strategy that can help restore the supply of green open Spaces on the green side of population, which is: optimize the water use areas to make green public Spaces, to use the removal of the land for public green Spaces, to use the ground in hill areas for use as open space. Public green areas such as parks or forests, and they promote and maintain the green facilities that support public activities.and maintaining reforestation of facilities that support community activities.